The Planning of Difficulty Curves in an Exergame for Inhibitory Control Stimulation in a School Intervention Program: A Pilot Study - Mossmann, João B.; Cerqueira, Bernardo B.; Barbosa, Débora N. F.; Fonseca, Rochele P.; Reategui, Eliseo B. (Frontiers in Psychology, 2019)
Apollo & Rosetta is an Exergame developed for Inhibitory Control stimulation in Elementary School children. This works' goal has been to demonstrate the behavior of the difficulty curves planned for seven activities (minigames) ingame, as well as their correspondence with the variables collected during a pilot neuropsychological intervention. Seven students participated in the study and played the minigames 1528 times during the 3-month intervention. Each of the minigames had a difficulty curve computed with the goal of keeping the players in the state of Flow. The curves were designed in cycles which grow throughout levels (Normal Level) to a peak (Peak Level), followed by a rest period (Rest Level). The pilot study encompassed three different analyses: (1) Exploratory performance analysis with Spearman correlation, which indicated a positive and significant general correlation between performance and level difficulty; (2) Success exploratory analysis, which showed that as the stages progressed, the success rate increased, even if the level difficulty also increased; (3) Analysis of the factors which influenced performance, through Mixed Effects Logistic Regression and the Backward method. This analysis demonstrated that the odds ratio for overcoming challenges between Normal levels was 0.71 [0.59;0.86] times lower than Rest Level (p-value=0.000), whereas in Peak levels it was 0.62 [0.47;0.83] times lower than Rest level values (p-value=0.001). These data confirm the overall planned behavior of the difficulty curves.